Genetic heterogeneity and clinical variability in musculocontractural Ehlers-Danlos syndrome caused by impaired dermatan sulfate biosynthesis - Syx, Delfien; Haußer-Siller, Ingrid (Human mutation, 2015)
Bi-allelic variants in CHST14, encoding dermatan 4-O-sulfotransferase-1 (D4ST1), cause musculocontractural Ehlers-Danlos syndrome (MC-EDS), a recessive disorder characterized by connective tissue fragility, craniofacial abnormalities, congenital contractures, and developmental anomalies. Recently, the identification of bi-allelic variants in DSE, encoding dermatan sulfate epimerase-1 (DS-epi1), in a child with MC-EDS features, suggested locus heterogeneity for this condition. DS-epi1 and D4ST1 are crucial for biosynthesis of dermatan sulfate (DS) moieties in the hybrid chondroitin sulfate (CS)/DS glycosaminoglycans (GAGs). Here, we report four novel families with severe MC-EDS caused by unique homozygous CHST14 variants and the second family with a homozygous DSE missense variant, presenting a somewhat milder MC-EDS phenotype. The glycanation of the dermal DS proteoglycan decorin is impaired in fibroblasts from D4ST1- as well as DS-epi1-deficient patients. However, in D4ST1-deficiency, the decorin GAG is completely replaced by CS, whereas in DS-epi1-deficiency, still some DS moieties are present. The multisystemic abnormalities observed in our patients support a tight spatiotemporal control of the balance between CS and DS, which is crucial for multiple processes including cell differentiation, organ development, cell migration, coagulation, and connective tissue integrity.